2022
DOI: 10.1186/s12877-022-03131-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of relational continuity of primary care in aged care: a systematic review

Abstract: Background Greater continuity of care has been associated with lower hospital admissions and patient mortality. This systematic review aims to examine the impact of relational continuity between primary care professionals and older people receiving aged care services, in residential or home care settings, on health care resource use and person-centred outcomes. Methods Systematic review of five databases, four trial registries and three grey litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…observed that older people who were attending on GP’s ambulatories indicated that pre-frailty and frailty are common conditions that should be identified early to allow effective and personalized management based on the multi-dimensional profile of the individual elderly, suggesting the very key role of a primary/family physician in geriatric care. [ 16 ] The quality of primary care becomes important because of an advanced age, disease complexity, and multi-morbidity, resulting in hospitalization which can be improved by interventions targeting primary care[ 17 30 ] and use of screening tools such as STOPP/START and Beers criteria by the primary/family physician.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…observed that older people who were attending on GP’s ambulatories indicated that pre-frailty and frailty are common conditions that should be identified early to allow effective and personalized management based on the multi-dimensional profile of the individual elderly, suggesting the very key role of a primary/family physician in geriatric care. [ 16 ] The quality of primary care becomes important because of an advanced age, disease complexity, and multi-morbidity, resulting in hospitalization which can be improved by interventions targeting primary care[ 17 30 ] and use of screening tools such as STOPP/START and Beers criteria by the primary/family physician.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] The quality of primary care becomes important because of an advanced age, disease complexity, and multi-morbidity, resulting in hospitalization which can be improved by interventions targeting primary care and use of screening tools such as STOPP/START and Beers criteria by primary or family physicians. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…Thus, patients are willing to actively provide accurate information to physicians. The accumulation of patient information means improved understanding of patient preferences [51], reduced counseling time [52], reduced diagnostic uncertainty [50], and increased patient satisfaction and adherence to treatment regimens, thus, facilitating the management of chronic diseases and reducing inpatient care [53][54][55][56][57]. Furthermore, with more complicated and serious diseases, general practitioners use their professional knowledge to promptly screen and refer the patient.…”
Section: Association Between Outpatient Visits Types and Er Or Hospit...mentioning
confidence: 99%
“…5 Coordinated and comprehensive primary health care has the potential to improve the overall health of older people and result in lower risk of hospitalisations and other health events. 6,7 Health assessments, GP management plans and team care arrangements for older people receiving home care packages or medication reviews for people living in permanent residential aged care (PRAC) have been found to be associated with lower mortality rates. 8,9 Despite the Australian Medical Association's 2018 Position Statement calling for a national evaluation of the access and effectiveness of primary care services in the care of older people to ensure their needs are being met, no such evaluation has occurred to date.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020–21, GPs were the most‐visited health professionals by the general population (>80% saw a GP) 5 . Coordinated and comprehensive primary health care has the potential to improve the overall health of older people and result in lower risk of hospitalisations and other health events 6,7 . Health assessments, GP management plans and team care arrangements for older people receiving home care packages or medication reviews for people living in permanent residential aged care (PRAC) have been found to be associated with lower mortality rates 8,9 …”
Section: Introductionmentioning
confidence: 99%